Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/su14052584
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–Temporal Differentiation and the Driving Mechanism of Rural Transformation Development in the Yangtze River Economic Belt

Abstract: Rural transformation development is an important part of rural revitalization, and the study of spatial–temporal differentiation characteristics and the driving mechanism of rural transformation development can provide a decision-making reference for formulating rural revitalization programs according to local conditions. Taking the Yangtze River Economic Belt as the research case, we constructed an evaluation system of rural transformation development in the dimension of “population, land and industry”, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…[9] Another view is that the differences and contradictions between urban and rural areas in economic, social, cultural and other aspects are the main driving force for promoting the integrated development of urban and rural areas. [10] From the perspective of existing literature research, most of them have studied the connotation, influencing factors, measurement methods, and mechanism of urban-rural integration from different research dimensions, and few literatures have systematically sorted out and identified the internal mechanism of digital economy and urban-rural integration in the context of the digital age. Therefore, this paper studies the marginal contribution of the digital economy to the integration of urban and rural areas.…”
Section: Discussion On Urban-rural Integrationmentioning
confidence: 99%
“…[9] Another view is that the differences and contradictions between urban and rural areas in economic, social, cultural and other aspects are the main driving force for promoting the integrated development of urban and rural areas. [10] From the perspective of existing literature research, most of them have studied the connotation, influencing factors, measurement methods, and mechanism of urban-rural integration from different research dimensions, and few literatures have systematically sorted out and identified the internal mechanism of digital economy and urban-rural integration in the context of the digital age. Therefore, this paper studies the marginal contribution of the digital economy to the integration of urban and rural areas.…”
Section: Discussion On Urban-rural Integrationmentioning
confidence: 99%
“…Using a broader set of relevant parameters may enhance the validity of the results. Indeed, the economic development prospects in FDAs, particularly in those near urban areas, present a compelling aspect for examination, and this will be the focus of our forthcoming research [57,58].…”
Section: Limitations and Future Prospectsmentioning
confidence: 99%
“…While the evaluation process is becoming more and more normalized, some scholars have proposed that the research area and research perspective do not have the same character, and the 20-character policy should be modified and integrated based on practical situations to complete the indicator layer's construction. Zhang Rongtian et al measured the rural development level of 41 prefecture-level cities in the Yangtze River Delta region by combining the three dimensions of "population development", "industrial development", and "land use" [20]; Zhang Qi et al built a nationwide rural development measurement framework based on the goal of common prosperity with three logics of "theory", "history", and "practice" [21]. In terms of research on the spatial differentiation of rural development, Lv Chengchao et al used the spatial range model to explore the spatial difference of rural development quality in 34 provinces of China [22], while Zhang Wang et al used the spatial autocorrelation model to measure the spatial pattern of rural development from the provincial perspective [23], and some scholars have used hot and cold point analysis or cluster analysis to study local clustering [24].…”
Section: Introductionmentioning
confidence: 99%